IMPLEMENTATION OF THE MOST BELOVED WORSHIP OF ALLAH SUBHANAA SUBHANAHU WA TA’ALA - Ekawanti, Ekawanti; Hasan, Hasan (Al-Mirah: Jurnal Pendidikan Islam, 2019)
Methodology is not new in the discourse of Islamic Studies. Indeed, it has become important element in an era where quality works, maqnum opus, from mujtahid and mujaddid in the golden era from the third to the sixth century. However, traced in the topic of its core (material) is nothing but the "accumulation" of studies of Islamic substance which was previously the basic material (introductory). The material is even still up to now and will be studied as basic Islamic knowledge especially in the Islamic Higher Education in this country. However, the study of each of the basic Islamic sciences is presented "separately" from one another. However, the discourses offered are still material which is basic introduction or introduction